2016
DOI: 10.1111/tpj.13106
|View full text |Cite
|
Sign up to set email alerts
|

Potential targets of VIVIPAROUS1/ABI3‐LIKE1 (VAL1) repression in developing Arabidopsis thaliana embryos

Abstract: These authors contributed equally to this work. SUMMARYDeveloping Arabidopsis seeds accumulate oils and seed storage proteins synthesized by the pathways of primary metabolism. Seed development and metabolism are positively regulated by transcription factors belonging to the LAFL (LEC1, AB13, FUSCA3 and LEC2) regulatory network. The VAL gene family encodes repressors of the seed maturation program in germinating seeds, although they are also expressed during seed maturation. The possible regulatory role of VAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 71 publications
2
61
0
Order By: Relevance
“…Our ChIP results confirmed that a mutant form of HSI2 with a disrupted PHD domain fails to accumulate at the 5ʹ region of the AGL15 locus in vivo (Figure 6). Through RNA sequencing analysis, Schneider et al (2016) identified two HSI2 splice variants: a full-length form and a truncated form that lacks coding sequences for the PHD domain. Translation of the truncated HSI2 transcript would produce a protein variant, similar to HSL2 that contains intact B3, CW, and EAR motifs but lacks the PHD domain (Jia et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our ChIP results confirmed that a mutant form of HSI2 with a disrupted PHD domain fails to accumulate at the 5ʹ region of the AGL15 locus in vivo (Figure 6). Through RNA sequencing analysis, Schneider et al (2016) identified two HSI2 splice variants: a full-length form and a truncated form that lacks coding sequences for the PHD domain. Translation of the truncated HSI2 transcript would produce a protein variant, similar to HSL2 that contains intact B3, CW, and EAR motifs but lacks the PHD domain (Jia et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, two VAL1 splice variants have been identified through RNA sequencing analysis: a full-length form and a truncated form lacking the plant homeodomain-like domain similar to VAL3, which also lacks the plant homeodomain-like domain (Schneider et al, 2016). It is possible that truncated VAL1 and VAL3 target this group of genes, explaining their lack of up-regulation in val1/2 mutants.…”
Section: Interplay Of Atbmi1 With Other Pcg-related Factorsmentioning
confidence: 99%
“…There are not many known negative regulators involved in seed development (Jia et al, 2013). One of these repressors is VIVIPAROUS1/ABI3-LIKE1 (VAL1), which is known to repress genes involved in the embryonic program (Schneider et al, 2016) and is also positively regulated by FUS3 (Wang and Perry, 2013). VAL1 was not differentially expressed above the cutoff (see Section Materials and Methods, above), so the VAL1 gene was absent from any clusters.…”
Section: Resultsmentioning
confidence: 99%
“…This data set contains the expression profiles of a total of 53,989 transcripts expressed in embryos of different ages represented by seven time points (7, 8, 10, 12, 13, 15, and 17 days after pollination (DAP) in three biological and four technical replicates; Schneider et al, 2016). Expression of these transcripts was normalized using fragments per kilobase of transcript per million mapped reads (FPKM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation